2007
DOI: 10.1152/ajpheart.00085.2007
|View full text |Cite
|
Sign up to set email alerts
|

Diaphragm single-fiber weakness and loss of myosin in congestive heart failure rats

Abstract: Diaphragm weakness commonly occurs in patients with congestive heart failure (CHF) and is an independent predictor of mortality. However, the pathophysiology of diaphragm weakness is poorly understood. We hypothesized that CHF induces diaphragm weakness at the single-fiber level by decreasing myosin content. In addition, we hypothesized that myofibrillar Ca(2+) sensitivity is decreased and cross-bridge kinetics are slower in CHF diaphragm fibers. Finally, we hypothesized that loss of myosin in CHF diaphragm we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
106
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(124 citation statements)
references
References 61 publications
(87 reference statements)
16
106
1
1
Order By: Relevance
“…The loss of diaphragm function during the development of HF may therefore be due, in part, to changes to the contractile elements of the muscle fibers composing the diaphragm. Previous work has demonstrated that the diaphragm of rats in end-stage heart failure can contain less myosin (66) and increased levels of myosin heavy chain oxidation (8). These studies indicate that the myofilament is playing a role in diaphragm dysfunction during heart failure.…”
Section: Diaphragmatic Myofilament Function Becomes Increasingly Impamentioning
confidence: 70%
See 1 more Smart Citation
“…The loss of diaphragm function during the development of HF may therefore be due, in part, to changes to the contractile elements of the muscle fibers composing the diaphragm. Previous work has demonstrated that the diaphragm of rats in end-stage heart failure can contain less myosin (66) and increased levels of myosin heavy chain oxidation (8). These studies indicate that the myofilament is playing a role in diaphragm dysfunction during heart failure.…”
Section: Diaphragmatic Myofilament Function Becomes Increasingly Impamentioning
confidence: 70%
“…Indeed, this work suggests, for the first time, that a decrease in the phosphorylation state of multiple myofilament proteins may be involved in initiating diaphragm dysfunction during the development of heart failure. Previously, loss of myosin content (66) and/or the increased levels of myosin heavy chain oxidation (8) have been described. While we did not observe any change in total myosin heavy chain content, given the progressive nature of the disease, our results do not preclude this from occurring at a later stage.…”
Section: Discussionmentioning
confidence: 99%
“…According to previously described methods (5,13), single fiber contractile measurements and experimental protocol were performed as follows.…”
Section: Single Fiber Contractile Measurementsmentioning
confidence: 99%
“…Impaired force generation of the respiratory muscles has been recognized in a variety of diseases, including chronic obstructive pulmonary disease (COPD) and congestive heart failure, and in critically ill patients (1)(2)(3)(4)(5)(6)(7). The pathophysiological substrate of diaphragm dysfunction in these disorders is multifactorial and includes muscle fiber atrophy and contractile protein dysfunction (3,(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…In other words, more calcium is needed to develop the same amount of force as in the non-COPD diaphragm, resulting in impaired contractile efficiency of the diaphragm muscle. Subsequent studies have shown that calcium sensitivity is also reduced in the diaphragm of animal models of congestive heart failure and prolonged mechanical ventilation (2,13). Despite a better understanding of respiratory muscle dysfunction in chronic diseases, no drug is available to improve respiratory muscle function in humans.…”
mentioning
confidence: 99%